Servicios públicos y remunicipalización - Tornos Mas, Joaquín (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
It is difficult to define the legal concept of public service. There are two ways to understand it. The first one is objective and tries to determine which activities and services should be guaranteed to all citizens with the aim of social cohesion. The second one is subjective and is based on the idea that public services are activities excluded from the market. This second conception emphasizes the problems arising from the relationship between the public and private sectors rather than the right of the citizenship to receive specific services. Within this general conceptual framework, this work shows the current debate which is not centered on which kinds of public services are to be provided but rather on how they have to be provided. The debate has a strong ideological content and defends the return to public management at the expense of private management, which is considered inefficient. This work analyzes the debate and introduces some objections to remunicipalization.

El concepto jurídico de servicio público es de difícil precisión. Existen dos concepciones de servicio público: una objetiva, preocupada por determinar qué actividades prestacionales deben ser garantizadas a todos los ciudadanos con el fin de lograr la cohesión social, y otra de carácter subjetivo, basada en la idea de que el servicio público es la actividad excluida del régimen de mercado, incidiendo sobre todo en los problemas de la relación entre sector público y sector privado más que en los derechos de los ciudadanos a obtener unas determinadas prestaciones. Dentro de este marco general conceptual, el presente trabajo pone de manifiesto como en la actualidad se ha abierto un debate de fuerte contenido ideológico en el que no se debate sobre qué servicios deben prestarse, sino sobre cómo deben prestarse los servicios públicos, defendiendo la recuperación de la gestión pública frente a una gestión privada que se califica de ineficiente. El trabajo analiza este debate y formula algunas objeciones a la tesis de la llamada «remunicipalización».
Public services and remunicipalization
Keywords: Municipalización; Remunicipalización; Rescate; Servicio económico de interés general; Servicio público; https://purl.org/pe-repo/ocde/ford#5.05.00